This is my story: An early career professor’s experience using a feedforward teaching method - Button, Brenton (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2023)
This Note from the Field is a reflection on the author’s first attempt at using a combined feedforward and agile teaching approach. Typically, professors receive student feedback at the end of a term through course evaluations. These evaluations can be powerful professional development tools, but the students who gave the feedback rarely benefit from their suggestions. Using a feedforward and agile approach may help professors integrate feedback during the semester and potentially increase student performance and/or engagement